The awareness profile regarding the disposal and reuse of solid waste of the University City, Federal University of Maranhão, MA, Brazil. - Figueiredo, Andréia de Queiroz dos Santos Abreu; Mendes, Mariana Bonfim Pinto; Nascimento, Aline Duarte; Vale, André Álvares Marques; Paiva, Brenda Hellen Izidio de; Saraiva Junior, Carlos Celso Frazão; Pereira, Diego Marinho; Araújo Júnior, Elias da Costa; Lima, Gustavo Pereira; Dutra, Itaynara Lobato; Silva, José Uilian da; Feitosa, Leonardo Manir; et al. (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
An important aspect the still absent in many universities is planning of disposal, storage and reuse of solid waste. The identification of situations faced by academic community regarding generation of waste is essential to the elaboration of programs, projects, systems and policies for sustainable management of generated waste. This study aimed to understand how aware of this issue is academic community of the University City, Federal University of Maranhão (UFMA), through a profile of the production of solid waste and its impacts on the environment. The methodology was based on the application of 509 questionnaires during the year 2011 in four different campuses centers, including 33 undergraduate and graduate departments from various fields, and six administrative centers. The questionnaires consisted of questions about recycling policies and waste sorting. According to our results, 67.97 % of respondents know the 3Rs (reduce, reuse and recycle) and 92.32 % said they would participate in a program for waste management if the university were to do so. However, over 60 % of respondents do not separate their household waste. Thus, it is important to note that, although encouraged by the university administration, an effective campaign should include the individual awareness of the academic body.